Progress in cryptology - INDOCRYPT 2011 12th international conference on cryptology in India, Chennai, India, December 11-14, 2011 : proceedings - Bernstein, Daniel J. (Daniel Julius) 1971-; Chatterjee, Sanjit (Springer, 2011)
This book constitutes the refereed proceedings of the 12th international conference on cryptology in India, INDOCRYPT 2011, held in Chennai, India, in December 2011. The 22 revised full papers presented together with the abstracts of 3 invited talks and 3 tutorials were carefully reviewed and selected from 127 submissions. The papers are organized in topical sections on side-channel attacks, secret-key cryptography, hash functions, pairings, and protocols.